Heparin-Induced Thrombocytopenia during Obstetric Hospital Admissions - Sagaram, Deepika; Siddiq, Zainab; Eisenberger, Andrew B.; Ananth, Cande V.; Wright, Jason D.; D'Alton, Mary E.; Friedman, Alexander M. (American Journal of Perinatology, 2018)
Introduction The rate of heparin-induced thrombocytopenia (HIT) on a population basis is unknown. The objective of this study was to characterize the risk for HIT during antepartum, delivery, and postpartum hospitalizations in the United States.Materials and Methods A large administrative database was used to determine the risk of HIT in hospitalized obstetric patients who received unfractionated heparin (UFH) or low molecular weight heparin (LMWH). Patients were presumed to have HIT if they were exposed to UFH or LMWH, received a diagnosis of HIT, and were administered a medication for the treatment of HIT including bivalirudin, argatroban, fondaparinux, or lepirudin. We queried severe complications of HIT including arterial thrombosis, limb amputation, heart failure, and death.Results We identified 66,468 antepartum hospitalizations, 66,741 delivery hospitalizations, and 16,325 postpartum readmissions where women received pharmacologic prophylaxis. Of these, 10 antepartum admissions, 1 delivery admission, and 14 postpartum readmissions involved a diagnosis of HIT with treatment of bivalirudin, argatroban, fondaparinux, or lepirudin. There were no deaths and no diagnoses of arterial thrombosis, limb amputation, heart failure, and death.Conclusion Risk for HIT among hospitalized obstetric patients is low. In this cohort, no cases of death or severe complications were noted in relation to the diagnosis.
Keywords: heparin-induced thrombocytopenia; obstetric thromboembolism; thromboembolism prophylaxis